THE USE OF SCHEMATA IN READING COMPREHENSION: A CASE OF LEARNERS' READING PROBLEMS - Cucu Sutarsyah (Universitas Negeri Malang, 2016)
The Use of Schemata in Reading Comprehension: A Case of Learners' Reading Problems. Schemata have an important role in the process of reading. It is almost impossible for a person to read without utilizing schemata. This study aimed to find learners' reading problem in terms of using schemata.  A group of second year students of English Department of State University of Malang were involved in this study. As a case study, an interview, observation, and test were used to collect the data. The study reveals that the main reading problems were lack of background knowledge, over-reliance on background knowledge, and lack of background knowledge activation. In the process of reading, learners' background knowledge should be activated. Without optimal activation, the process of reading does not reach satisfactory results. It is also suggested that learners should not be over confident in getting the meaning from the text. Over-reliance on background knowledge might lead to misinterpretation.